GANGGUAN MENTAL ISTRI SEBAGAI ALASAN IZIN POLIGAMI (Tinjauan Hukum Islam atas Putusan Perkara di Pengadilan Agama Magelang No. 11/Pdt.G/2023/PA.Mgl) - Rochi, Shanti Maharanti; Mubarok, M. Ali (Al'Adalah, 2023)
This study discusses the considerations of the judges of the Magelang Religious Court in granting permission for polygamy. In this case, the applicant applied for permission to practice polygamy because his first wife had a mental disorder. This study aims to determine judges' Islamic legal considerations in making decisions. This type of research is library research, using an analytical descriptive approach. The panel of judges, in their decision, apart from being based on the juridical aspect, also referred to the rule of fiqh: "If there are two evils threatening each other, then watch out for the one with the greater evil by carrying out the one with the least evil," then granted the petitioner's request because it was judged that the evil was much smaller than rejecting it. The petitioner's ability to act reasonably towards their wives and children is also considered to have met the requirements for polygamy as emphasized in the Qur’an (surah al-Nisa [4]: 3), so that the granting of permission for polygamy by the panel of judges is following Islamic Law and not against Indonesian Law.